THE NEW PARADIGM OF MEDICAL ENGLISH TEACHING AT THE UNIVERSITY LEVEL - Wiertlewska, Janina (Scripta Neophilologica Posnaniensia, 2019)
Currently practised methods of medical English instruction at tertiary education level often focus on medical terminology embedded in the English language classes. These strategies which comprise medical terminology and simple dialogues do not meet the needs of highly qualified medical health care workers (doctors, nurses, paramedics and many others). The new paradigm claims that medical English should be taught from the perspective of medicine and health care first and reinforced by the vocabulary acquisition; first – teach the students standards of medical practice (anatomy, pharmacology, physiology, medical sciences. and behavioural/ethical procedures), later on – concentrate on medical communication (see: M. Hull, 2004). The following paper concentrates on both formerly mentioned parameters; and also includes student and teacher motivation. Further, language acquisition as well as language learning are discussed. The new paradigm is defined as a combination of academic preparation which comprises cognitive and behavioural approaches that appear to be secondary to the context of the given class. Students are encouraged to search for synonyms, abbreviations and alternative ways of expressing meaning to communicate with each other. They also prepare their own multimedia presentations in the group and deliver speeches on subjects contained in curriculum. Concluding, the author of this paper expresses the opinion that foundational underpinnings of the curriculum of the Medical English course should be linked to the parameters for the health care professions. Context of the classes needs to be relevant to the work of the health professionals (according to Pratt and others, 2002). Over the last 10 years the paradigm for medical English teaching in North America and West European countries has changed enormously and has started to pave its new way at tertiary education level in Poland as well, which is presented briefly in this paper and – hopefully will continue to develop according to the newly occurring phenomena.